دور الزعامة الدينية في الاحداث السياسية العراقية الزعامة الدينية في كربلاء "إنموذجاً" (1918 – 1922 م) - سعيد عبود, وسن (Al-Adab Journal, 2018)
The study concluded that Shiite religious leadership in the holy city of Karbala during the period (1918-1922) has exercised an important role in the moder history of Iraq that role, which spread in the religious, political and social paths, putting in mind several key objectives, namely: -fight the British occupation as a foreign non-Muslim.leadership politically, militarily and religiously the people of Karbala during the pre-stage of the monarchy, and its leadership has expanded to include the bulk of the Shiite masses and thus may be able to fill a large part of the vacuum in the Iraqi arena.able to move the compass awareness darkening the nation from dependence to feudal landlords and adults to rally around as a real mentor of the nation.Those able leadership create an atmosphere of cooperation between the Iraqi people and specifically components Sunni and Shiite.The establishment of the monarchy in Iraq, one of the goals sought religious leadership to achieve, but the King Faisal first decision of the signing of the 1922 treaty with the British, including in respect of exploitation and dominance of the country is the relationship between the king and his government on the part of religious leaders equation from the other side and ended this change for the first party and the deportation of many religious leaders outside of Iraq because of their involvement in the political Affairs is welcomed. Finally, the study began to stage a historic mission lived in the city of Karbala under the religious leaders and the study concluded sad incident on the city of Karbala, a displacement of the most prominent religious leaderships outside Iraq.